1999
DOI: 10.1021/bi982793w
|View full text |Cite
|
Sign up to set email alerts
|

Substitution Studies of the Second Divalent Metal Cation Requirement of Protein Tyrosine Kinase CSK

Abstract: In addition to a magnesium ion needed to form the ATP-Mg complex, we have previously determined that at least one more free Mg 2+ ion is essential for the activation of the protein tyrosine kinase, Csk [

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(60 citation statements)
references
References 34 publications
1
59
0
Order By: Relevance
“…There are also serine/threonine kinases that can be activated by Mn 2ϩ (37,40). This effect is most likely because of the binding of Mn 2ϩ instead of Mg 2ϩ to the second metalbinding site (31,39). At the same time, it was demonstrated that binding of Zn 2ϩ or Co 2ϩ at this second binding site is inhibitory in tyrosine kinases (39).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are also serine/threonine kinases that can be activated by Mn 2ϩ (37,40). This effect is most likely because of the binding of Mn 2ϩ instead of Mg 2ϩ to the second metalbinding site (31,39). At the same time, it was demonstrated that binding of Zn 2ϩ or Co 2ϩ at this second binding site is inhibitory in tyrosine kinases (39).…”
Section: Discussionmentioning
confidence: 99%
“…This effect is most likely because of the binding of Mn 2ϩ instead of Mg 2ϩ to the second metalbinding site (31,39). At the same time, it was demonstrated that binding of Zn 2ϩ or Co 2ϩ at this second binding site is inhibitory in tyrosine kinases (39). A striking similarity between the effects of divalent metal ions on ChaK1-cat activity and tyrosine kinases suggests that the catalytic mechanism of phosphotransfer in ␣-kinases and conventional protein kinases may be similar.…”
Section: Discussionmentioning
confidence: 99%
“…Two cation binding sites in the active site of kinases have been defined, and binding of cations to the second, lower affinity site can either be stimulatory or inhibitory (25)(26)(27). It was previously reported that Her4 kinase activity is higher in the presence of Mn 2ϩ than with Mg 2ϩ , but that Mn 2ϩ concentrations Ͼ0.5 mM resulted in a reduction in Her4 kinase activity (28).…”
Section: Her4 Kinase Domain Is Activated By Dimerizing On the Surfacementioning
confidence: 99%
“…The group IIB metal ions are of great interest because Zn 21 , one of the most abundant divalent metal ions in living organisms, 1 is an essential cofactor in many metabolic enzymes and transcription factors. [2][3][4][5][6][7][8] On the other hand, Cd 21 and Hg 21 , which are in the same periodic group as Zn 21 , are known to be toxic to living organisms.…”
Section: Introductionmentioning
confidence: 99%